Increasing plant performance, fruit production and nutritional value of tomato through foliar applied rutin - Gorni, Pedro Henrique; de Lima, Gustavo Rios; Pereira, Lucia Maria de Oliveira; Spera, Kamille Daleck [UNESP]; Lapaz, Allan de Marcos; Pacheco, Ana Cláudia (Elsevier, 2022)
Rutin is a widely distributed natural flavonoid in higher plants and is considered a signal molecule responsible for inducing defense responses against biotic and abiotic stresses. This study evaluated the effect of foliar spray of rutin (0, 0.5, 1.0, 1.5, and 2.0 mmol L−1) 20 days after transplanting the seedlings to the pots, in three consecutive applications. The effect of rutin on the metabolism of tomato plants was evaluated through on photosynthetic performance, crop development and yield, fruit bioactive compounds, and antioxidant activity in tomato variety ‘IPA 6’. Beneficial effects of rutin in tomato are associated with increased photosynthetic performance and higher concentration of leaf primary metabolites, such as chlorophyll, carbohydrates, and protein; which provides evidence for improved plant growth parameters and fruit production. At the same time, rutin pulverization also resulted in a higher concentration of secondary compounds in tomato fruits such as polyphenol, flavonoid, lycopene, β-carotene, and lutein, providing them a greater antioxidant capacity. Cross-talks among plant physiological responses, fruit production and fruit quality as a result of rutin application implicates the benefits of using this elicitor for sustainable commercial cultivation of Solanum lycopersicum.
Keywords: elicitation; lycopene; secondary metabolites; Solanum lycopersicum; β-carotene